Indian summer monsoon drought 2009: role of aerosol and cloud microphysics. (17th May 2013) - Hazra, A.; Taraphdar, S.; Halder, M.; Pokhrel, S.; Chaudhari, H. S.; Salunke, K.; Mukhopadhyay, P.; Rao, S. A.
Abstract: Cloud dynamics played a fundamental role in defining Indian summer monsoon (ISM) rainfall during drought of 2009. The anomalously negative precipitation was consistent with cloud properties. Although, aerosols inhibited the growth of cloud effective radius in the background of sparse water vapor, their role is secondary. The primary role, however, is played by the interactive feedback between cloud microphysics and dynamics owing to reduced efficient cloud droplet growth, lesser latent heating release and shortage of water content. Cloud microphysical processes were instrumental for the occurrence of ISM drought 2009.